Physicochemical and dissolution profile characterization of pellets containing different binders obtained by the extrusion-spheronization process - Michele Georges Issa; Letícia Pessole; Andrea Ikeda Takahashi; Newton Andréo Filho; Humberto Gomes Ferraz (Universidade de São Paulo, 2012)
With the purpose of evaluating the behavior of different polymers employed as binders in small-diameter pellets for oral administration, we prepared formulations containing paracetamol and one of the following polymers: PVP, PEG 1500, hydroxypropylmethylcellulose and methylcellulose, and we evaluated their different binding properties. The pellets were obtained by the extrusion/spheronization process and were subsequently subjected to fluid bed drying. In order to assess drug delivery, the United States Pharmacopeia (USP) apparatus 3 (Bio-Dis) was employed, in conjunction with the method described by the same pharmacopeia for the dissolution of paracetamol tablets (apparatus 1). The pellets were also evaluated for granulometry, friability, true density and drug content. The results indicate that the different binders used are capable of affecting production in different ways, and some of the physicochemical characteristics of the pellets, as well as the dissolution test, revealed that the formulations acted like immediate-release products. The pellets obtained presented favorable release characteristics for orally disintegrating tablets. USP apparatus 3 seems to be more adequate for discriminating among formulations than the basket method. Com a finalidade de se avaliar o comportamento de diferentes polímeros empregados como aglutinantes em pellets de pequeno diâmetro para uso oral foram preparadas formulações contendo paracetamol e um dos seguintes polímeros: PVP, PEG 1500, hidroxipropilmetilcelulose e metilcelulose por apresentarem diferentes propriedades aglutinantes. Os pellets foram obtidos pelo processo de extrusão/esferonização e secagem em leito fluidizado. Para avaliar a liberação do fármaco, empregou-se o método 3 da Farmacopeia Americana, também conhecido como Bio-Dis e o método preconizado pela mesma farmacopeia para comprimidos de paracetamol. Os pellets foram avaliados, ainda, com relação à granulometria, friabilidade, densidade verdadeira e teor. Os resultados indicaram que os diferentes aglutinantes empregados são capazes de afetar a produção e algumas das características físico-químicas dos pellets e o ensaio de dissolução revelou que as formulações comportam-se como produtos de liberação imediata. Os pellets obtidos apresentaram características de liberação favoráveis para a obtenção de comprimidos de liberação instantânea. O aparato 3 da Farmacopeia Americana demonstrou ser um método com melhor capacidade discriminatória entre as formulações, quando comparado com o método da cesta.